The role of the Ventral Nucleus of the Trapezoid Body in the auditory prepulse inhibition of the acoustic startle reflex - Barioni, N. O. [UNESP]; Beduschi, R. S. [UNESP]; da Silva, A. V.; Martins, M. G. [UNESP]; Almeida-Francia, C. C.D. [UNESP]; Rodrigues, S. A. [UNESP]; López, D. E.; Gómez-Nieto, R.; Horta-Júnior, J. A.C. [UNESP] (Elsevier, 2024)
Cholinergic signaling is essential to mediate the auditory prepulse inhibition (PPI), an operational measure of sensorimotor gating, that refers to the reduction of the acoustic startle reflex (ASR) when a low-intensity, non-startling acoustic stimulus (the prepulse) is presented just before the onset of the acoustic startle stimulus. The cochlear root neurons (CRNs) are the first cells of the ASR circuit to receive cholinergic inputs from non-olivocochlear neurons of the ventral nucleus of the trapezoid body (VNTB) and subsequently decrease their neuronal activity in response to auditory prepulses. Yet, the contribution of the VNTB-CRNs pathway to the mediation of PPI has not been fully elucidated. In this study, we used the immunotoxin anti-choline acetyltransferase (ChAT)-saporin as well as electrolytic lesions of the medial olivocochlear bundle to selectively eliminate cholinergic VNTB neurons, and then assessed the ASR and PPI paradigms. Retrograde track-tracing experiments were conducted to precisely determine the site of lesioning VNTB neurons projecting to the CRNs. Additionally, the effects of VNTB lesions and the integrity of the auditory pathway were evaluated via auditory brain responses tests, ChAT- and FOS-immunohistochemistry. Consequently, we established three experimental groups: 1) intact control rats (non-lesioned), 2) rats with bilateral lesions of the olivocochlear bundle (OCB-lesioned), and 3) rats with bilateral immunolesions affecting both the olivocochlear bundle and the VNTB (OCB/VNTB-lesioned). All experimental groups underwent ASR and PPI tests at several interstimulus intervals before the lesion and 7, 14, and 21 days after it. Our results show that the ASR amplitude remained unaffected both before and after the lesion across all experimental groups, suggesting that the VNTB does not contribute to the ASR. The%PPI increased across the time points of evaluation in the control and OCB-lesioned groups but not in the OCB/VNTB-lesioned group. At the ISI of 50 ms, the OCB-lesioned group exhibited a significant increase in%PPI (p < 0.01), which did not occur in the OCB/VNTB-lesioned group. Therefore, the ablation of cholinergic non-olivocochlear neurons in the OCB/VNTB-lesioned group suggests that these neurons contribute to the mediation of auditory PPI at the 50 ms ISI through their cholinergic projections to CRNs. Our study strongly reinforces the notion that auditory PPI encompasses a complex mechanism of top-down cholinergic modulation, effectively attenuating the ASR across different interstimulus intervals within multiple pathways.
Keywords: Auditory prepulse inhibition pathway; Cholinergic projections; Cochlear root neurons; Saporin immunolesion; Sensorimotor gating